Analysis of patent registries in Brazilian nursing and its relationship with the professional master's degree - Cláudio José de Souza; Zenith Rosa Silvino; Deise Ferreira de Souza (Universidade Federal do Rio Grande do Sul, 2020)
ABSTRACT Objective: To analyze the patent registrations registered in the nursing area from 2004 to 2019, relating to the beginning of the Professional Masters in Nursing. Method: Electronic documentary research carried out at the bases of the National Institute of Industrial Property and Lattes Platform. After data collection, requests, filing date, patent titles, international patent classification and areas of expertise of depositor / inventors were analyzed. Results: The study points out that there was no significant correlation between the number of registered patents with the prelude to the professional master's degree in nursing, corroborating with previous studies regarding incipience. Final considerations: although two of the initial objectives of professional master's programs are creation and technological innovation, it is analyzed that the granted institutions need to simplify and equip researchers with regard to the patent registration process, so that we can take off in this technological universe.